2022
DOI: 10.1111/1748-8583.12471
|View full text |Cite
|
Sign up to set email alerts
|

What does democratic management do in Chinese workplaces? Evidence from matched employer–employee data

Abstract: Democratic management (DM) is an important set of statutory employee participation institutions that goes beyond trade unions in Chinese workplaces; however, its effects on pay and performance are unstudied. Using data from the China Employer-Employee Matched Survey, this study examines how DM is associated with pay and performance levels in China. The study finds that DM is positively associated with workers' hourly wages, fringe benefits, and firms' labour productivity on average, suggesting that it is not m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…The nature of these arrangements is input democracy (consultation) rather than output democracy (joint decision-making) (Huang, 2022). Recent studies have reported the effectiveness of China's democratic management (Chen et al, 2022; Huang et al, 2016; Jing et al, 2022; Long et al, 2021). This is in contrast to earlier research on democratic management under Mao's regime and the democratising workplace reform of the 1980s.…”
Section: Introductionmentioning
confidence: 99%
“…The nature of these arrangements is input democracy (consultation) rather than output democracy (joint decision-making) (Huang, 2022). Recent studies have reported the effectiveness of China's democratic management (Chen et al, 2022; Huang et al, 2016; Jing et al, 2022; Long et al, 2021). This is in contrast to earlier research on democratic management under Mao's regime and the democratising workplace reform of the 1980s.…”
Section: Introductionmentioning
confidence: 99%